The communicative management of media activity between Spain and Germany in the context of the crisis of the cucumbers. - Vázquez Gestal, Montse; Fernández Souto, Ana Belén (Historia y Comunicación Social, 2014)
Treatment media received the crisis of cucumbers between Spain and Germany, developed during the year 2011, above all during the month of may, emphasized that not only was a food crisis, but an institutional and international crisis in which the German authorities and their media rowed in the same direction so that the Spanish product and there fore Spain drop its image internationally.